THE ANALYSIS OF TEACHERS’ STRATEGIES FOR VOCABULARY AT SDN BAKALAN II KAPAS - Chyntia Heru Woro Prastiwi; Meiga Ratih Tirtanawati; Sari, Vera Lutviya (Universitas Aisyah Pringsewu, 2024)
Teacher strategy is the most important technique in teaching vocabulary. Teaching strategies aim to make it easier for teachers to choose the methods used to help students learn the desired subject matter and develop goals that will be achieved in the future. There are many strategies that teachers can use to teach vocabulary, one of which is games. The purpose of this research is to analyze what strategies teachers use and how to implement the strategies they use when teaching English vocabulary. This research focuses on 3 teachers based on the length of teaching experience at SDN Baklan II Kapas. In this research, researchers collected data using direct interviews with teachers at SDN Bakalan II Kapas. This study's results reveal several strategies teachers use when teaching in the classroom.